Association of chest compression pause duration prior to E-CPR cannulation with cardiac arrest survival outcomes. (August 2022) - Lauridsen, Kasper G.; Lasa, Javier J.; Raymond, Tia T.; Yu, Priscilla; Niles, Dana; Sutton, Robert M.; Morgan, Ryan W.; Fran Hazinski, Mary; Griffis, Heather; Hanna, Richard; Zhang, Xuemei; Berg, Robert A.; et al.
Abstract: Objective: To characterize chest compression (CC) pause duration during the last 5 minutes of pediatric cardiopulmonary resuscitation (CPR) prior to extracorporeal-CPR (E-CPR) cannulation and the association with survival outcomes. Methods: Cohort study from a resuscitation quality collaborative including pediatric E-CPR cardiac arrest events ≥ 10 min with CPR quality data. We characterized CC interruptions during the last 5 min of defibrillator-electrode recorded CPR (prior to cannulation) and assessed the association between the longest CC pause duration and survival outcomes using multivariable logistic regression. Results: Of 49 E-CPR events, median age was 2.0 [Q1, Q3: 0.6, 6.6] years, 55% (27/49) survived to hospital discharge and 18/49 (37%) with favorable neurological outcome. Median duration of CPR was 51 [43, 69] min. During the last 5 min of recorded CPR prior to cannulation, median duration of the longest CC pause was 14.0 [6.3, 29.4] sec: 66% >10 sec, 25% >29 sec, 14% >60 sec, and longest pause 168 sec. Following planned adjustment for known confounders of age and CPR duration, each 5-sec increase in longest CC pause duration was associated with lower odds of survival to hospital discharge [adjusted OR 0.89, 95 %CI: 0.79–0.99] and lower odds of survival with favorable neurological outcome [adjusted OR 0.77, 95 %CI: 0.60–0.98]. Conclusions: Long CC pauses were common during the last 5 min of recorded CPR prior to E-CPR cannulation. Following adjustment for age and CPR duration, each 5-second incremental increase in longest CC pause duration was associated with significantly decreased rates of survival and favorable neurological outcome.